Dynamic response of 3d-printed acrylonitrile butadiene styrene (abs) damaged structure under thermo-mechanical loads. - He, Feiyang (Cranfield University, 2021)
Fused deposition modelling (FDM), as the most widely used additive manufacturing (AM) process, has great potential for various applications. The structures manufactured with the FDM technique has the potential to be used in a variety of complex working environments, such as the coupled thermo- mechanical loads. The coupled thermo-mechanical loads can likely lead to fatigue cracking swiftly in structures till the catastrophic failure. Therefore, it is critical to research the fatigue crack behaviour in FDM structures. This behaviour is mainly responsible for the change of structural stiffness and hence can influence the dynamic response of the structure under the mentioned loads. The measurement of the structural dynamic response can give us an idea of the severity due to crack growth in an in-situ manner. This thesis mainly aims to investigate the dynamic response of the cracked FDM structures under thermo- mechanical loads. The relationship between the coupled loads, crack propagation and dynamic response is developed analytically and later validated experimentally. This research has improved the existing torsional spring model, which can represent the crack depth more accurately and hence estimated the fundamental frequency of the selected structure with an up to around 20% to 120% reduced error in the case of deep cracks. Furthermore, the analytical relationship between the structural displacement amplitude and crack depth and location was modelled for the very first time in the presence of the crack breathing effect. Extensive experimentation is performed to validate the developed analytical relationship and its related theory. The fatigue crack growth of FDM ABS beams under thermo-mechanical loads with varying printing parameters is also investigated. The optimal printing parameters combination (X raster orientaion, 0.8 mm nozzle size, 0.15 mm layer thickness) is determined. The underlying reasons behind the experimental data are analysed. The outcome of this optimisation can help manufacturers to print long-life and crack resistant printed structures.
Starr, Andrew - Associate Supervisor
Keywords: Fused deposition modelling; ABS; fatigue; crack growth; dynamic response; thermo-mechanical loads